Multidimensional study of the oral microbiome, metabolite, and immunologic environment in peanut allergy - Ho, Hsi-en; Chun, Yoojin; Jeong, Stephanie; Jumreornvong, Oranicha; Sicherer, Scott H.; Bunyavanich, Supinda (Journal of allergy and clinical immunology, 2021)
The oral mucosa is the initial interface between food antigens, microbiota, and mucosal immunity, yet, little is known about oral host-environment dynamics in food allergy. Our aim was to determine oral microbial, metabolic, and immunologic profiles associated with peanut allergy. We recruited 105 subjects (56 with peanut allergy and 49 healthy subjects) for salivary microbiome profiling using 16S ribosomal RNA sequencing, short-chain fatty acid (SCFA) metabolite assays using liquid chromatography/mass spectrometry, and measurement of oral secreted cytokines using multiplex assays. Analyses within and across data types were performed. The oral microbiome of individuals with peanut allergy was characterized by reduced species in the orders Lactobacillales, Bacteroidales (Prevotella spp), and Bacillales, and increased Neisseriales spp. The distinct oral microbiome of subjects with peanut allergy was accompanied by significant reductions in oral SCFA levels, including acetate, butyrate, and propionate, and significant elevation of IL-4 secretion. Decreased abundances of oral Prevotella spp and Veillonella spp in subjects with peanut allergy were significantly correlated with reduced oral SCFA levels (false discovery rate < 0.05), and increased oral Neisseria spp was correlated with lower oral SCFA levels (false discovery rate < 0.05). Additionally, oral Prevotella spp abundances were correlated with decreased local secretion of TH2–stimulating epithelial factors (IL-33 and thymic stromal lymphopoietin) and TH2 cytokines (IL-4, IL-5, and IL-13), whereas oral Neisseria spp abundance was positively associated with a TH2–skewed oral immune milieu. Our novel multidimensional analysis of the oral environment revealed distinct microbial and metabolic profiles associated with mucosal immune disturbances in peanut allergy. Our findings highlight the oral environment as an anatomic site of interest to examine host-microbiome dynamics in food allergy.